Her War: Women Vs. ISIS - Trofimova, Anastasia (Russia, 2015)
In the Syrian town of Serekaniye, the people live under constant threat from ISIS. The documentary explores the significant number of women who are leading the battle against the infamous terrorist organization.
Verzio Film Festival Submission
Keywords: Documentary films